Day-ahead scheduling of wind generation and energy storage - Mohamed, Shaaban; Wen-shan, Tan; Md Pauzi, Abdullah (2017)
This paper presents a chance-constrained scheduling (CCS) approach for variable wind generation, in the day-ahead timescale, including energy storage. The day-ahead CCS utilizes the ramping of conventional generation as well as the dispatch of energy storage to enhance the load following and ramping support capabilities, to mitigate the impact of net load ramps. The proposed CCS approach is converted into an equivalent mixed-integer linear programming (MILP) expression with the aim to maintain the compatibility with commercially state-of-the-art optimization solvers. Numerical simulations, carried out on the IEEE RTS 96 test system with high penetration of wind power, indicate the effectiveness of the developed CCS formulation and highlight the competitive aspects of the proposed CCS approach